Atmosfer Termodifikasi Tidak Memperpanjang Umur Simpan Bawang Bombay Kultivar Southport White Globe - Suharwadji Sentana (agriTECH, 2000)
This study was carried out to see the effect of modified atmosphere storage on the storage life of Southport White Globe (SWG) onions. SWG onions were packed in polyethylene bags and stored at 20°C for 14 weeks. To increase its effectiveness, phorone, KMnO4 and Ca(OH)2 at various levels were also placed inside the polyethylene bags. Production of CO2, O2 and ethylene were monitored fortnightly, and at the end of storage, onion sprouting, rotting, and rooting were also observed. The results show that phorone at 2 ml tended to stimulate CO2 production, while KMnO4, Ca(OH)2 at either 200 g or 400 g inhibited CO2 production, however, ethylene elimination tended to stable. No root growths were detected. Disease incidents were also prohibited by KMnO4, Ca(OH)2, and KMnO4 plus Ca(OH)2 at 400 g. On the other hand, those chemicals stimulated onion sprouting.